Manajemen Sumber Daya Manusia Dalam Meningkatkan Mutu Pendidikan - Zulwiddi, Neka; M, Iswantir (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
Education is the main factor in determining the level of quality of a country in facing the development of the global world. In practice, no matter how good the quality of human resources will not be able to run well if the management or management is not running well, so structured management is needed to help manage these human resources. The purpose of this research is to analyze human resource management in schools, while the research method used is qualitative method. The result of this study is that the school has implemented human resource management well. The obstacle is that human resource incentives are relatively low, so that the level of satisfaction in work does not run optimally.